Sheep in a jeep - Shaw, Nancy (Nancy E.); Apple, Margot (Boston : Houghton Mifflin, 1986)
Records the misadventures of a group of sheep that go riding in a jeep.
"Sandpiper Houghton Mifflin books."
Keywords: Stories in rhyme; Sheep -- Juvenile fiction